2012
DOI: 10.1371/journal.pone.0032300
|View full text |Cite
|
Sign up to set email alerts
|

Cd2+ Toxicity to a Green Alga Chlamydomonas reinhardtii as Influenced by Its Adsorption on TiO2 Engineered Nanoparticles

Abstract: In the present study, Cd2+ adsorption on polyacrylate-coated TiO2 engineered nanoparticles (TiO2-ENs) and its effect on the bioavailability as well as toxicity of Cd2+ to a green alga Chlamydomonas reinhardtii were investigated. TiO2-ENs could be well dispersed in the experimental medium and their pHpzc is approximately 2. There was a quick adsorption of Cd2+ on TiO2-ENs and a steady state was reached within 30 min. A pseudo-first order kinetics was found for the time-related changes in the amount of Cd2+ comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 37 publications
3
69
0
Order By: Relevance
“…Bioavailability and toxicity of n-TiO 2 for aquatic biota is well documented (Canesi et al, 2010a(Canesi et al, , 2010bGalloway et al, 2010;Menard et al, 2011;Mouneyrac et al, 2014;Frenzilli et al, 2014;Rocco et al, 2015). Besides the potential of n-TiO 2 to impact organisms directly through its inherent properties, it is also expected to interact with organic xenobiotics and heavy metals modifying their availability and/or toxicity (Zhang et al, 2007;Hu et al, 2011;Zhu et al, 2011;Hartmann et al, 2012;Yang et al, 2012). In our recent study both synergistic and antagonistic sub-lethal effects of n-TiO 2 towards 2, 3,7,3,7, including enhanced bioaccumulation were observed .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Bioavailability and toxicity of n-TiO 2 for aquatic biota is well documented (Canesi et al, 2010a(Canesi et al, , 2010bGalloway et al, 2010;Menard et al, 2011;Mouneyrac et al, 2014;Frenzilli et al, 2014;Rocco et al, 2015). Besides the potential of n-TiO 2 to impact organisms directly through its inherent properties, it is also expected to interact with organic xenobiotics and heavy metals modifying their availability and/or toxicity (Zhang et al, 2007;Hu et al, 2011;Zhu et al, 2011;Hartmann et al, 2012;Yang et al, 2012). In our recent study both synergistic and antagonistic sub-lethal effects of n-TiO 2 towards 2, 3,7,3,7, including enhanced bioaccumulation were observed .…”
Section: Introductionmentioning
confidence: 74%
“…Interaction between n-TiO 2 and heavy metals, particularly Cd 2þ , has been investigated in different freshwater models leading to conflicting results. In the green algae Chlamydomonas reinhardtii, n-TiO 2 reduced Cd 2þ accumulation and toxicity (Yang et al, 2012) while no influence on Cd 2þ uptake was observed on Lumbriculus variegates. TiO 2 -NPs were reported to increase Cd 2þ bioavailability and toxicity in Daphnia magna (Hartmann et al, 2012(Hartmann et al, , 2013Tan and Wang, 2014) and to enhance Cd 2þ bioaccumulation in zebrafish but this effect was reduced in the presence of humic acid (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have reported that n-TiO 2 can adsorb heavy metals [4,34,44] or organic toxicants, including tributyltin, PBDEs, DDT and tetrachlorodibenzo-p-dioxin [TCDD] [12,13,45,46], while study showed the aggregation and subsequent sedimentation of nTiO 2 with tributyltin [12]. At the same time, we did not measure and (E) GSH content in larvae after exposure to PCP alone (0, 3, 10, and 30 g/L) and in the presence of n-TiO2 (0.1 mg/L) for 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a mixture of NPs and other environmental toxicants is present in the environment. In this regard, NPs are highly insoluble and have a large surface area to volume ratio, suggesting that they are likely to interact with other substances in water [2][3][4]. Thus, NPs organic contaminants and enhances the uptake of organic pollutants (e.g., tributyltin, polybrominated diphenyl ethers [PBDEs]) in organisms [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In D. magna increased Cd 2þ bioavailability has been reported in the presence of n-TiO 2 (Hartmann et al, 2012). However, in the green algae Chlamydomonas reinhardtii, Cd 2þ toxicity as well as accumulation seemed to be reduced by n-TiO 2 (Yang et al, 2012), and no influence of n-TiO 2 was observed on Cd 2þ uptake on Lumbriculus variegatus (Hartmann et al, 2012). In the freshwater bivalve Corbicula fluminea, Cd 2þ uptake and antioxidant biomarker responses were unaffected by the presence of n-TiO 2 , despite n-TiO 2 significantly reducing the free Cd 2þ content in the medium (Vale et al, 2014).…”
Section: Interactive Effects Of Carbon-based Nps With Other Contaminantsmentioning
confidence: 96%